Mapping Research Variables with the Big Theme Innovative Product New Universe - Salsabilla, Ghefira Sabrina; Nuraeni, Nova; Setiawan, Adi (Malikussaleh University, Aceh, Indonesia, 2025)
Innovative Products combine the latest technology and creative ideas to create efficient, sustainable, value-added solutions. With new features and a more personalized user experience, product innovation drives economic growth competitiveness and addresses global challenges. This research aims to identify articles that examine the role of innovative products in the context of the new universe and provide an understanding of innovative products as a creative approach to marketing. In addition, this research aims to show and explain research mapping that is relevant to this theme. This research uses qualitative methods with bibliometric techniques by utilizing Similarity Visualization (Vosviewers) as an application. By entering keywords such as Goods, Service, Event, Experience, People, Place, Ownership, Organization, and Information, The idea was to search for articles via Publish or Perish with a total of 468 articles, which were then processed using VosViewers. The results of the analysis found the scientific mapping and the possibility of future research regarding product innovation that could be used as a recommendation variable for future researchers as a reference for subsequent articles.